Endoscopic Management of Peptic Ulcer Bleeding: Recent Advances - Philip WY Chiu (Korean Society of Gastrointestinal Endoscopy, 2019)
Bleeding peptic ulcers remained as one of the commonest causes of hospitalization worldwide. While endoscopic hemostasis serves as primary treatment for bleeding ulcers, rebleeding after endoscopic hemostasis becomes more and more difficult to manage as patients are usually poor surgical candidates with multiple comorbidities. Recent advances in management of bleeding peptic ulcers aimed to further reduce the rate of rebleeding through-(1) identification of high risk patients for rebleeding and mortality; (2) improvement in primary endoscopic hemostasis and; (3) prophylactic angiographic embolization of major arteries. The technique and clinical evidences for these approaches will be reviewed in the current article.